iFREEPHONY: MINIMALISTIC INTERFACE DEVELOPED FOR THE VISUALLY IMPAIRED AND THE ELDERLY COMMUNITY IN BANGLADESH (Journal of Information and Communication Technology, 2017)
Touchscreen-based phones can be challenging for people with visual impairment. These phones require special features to cater to their needs when it comes to a developing countryâ€™s perspective like Bangladesh. The interface needs to remain simple as well as it must support the required functionalities. It is often observed that touchscreen phones are not desirable for the user community in Bangladesh as it offers a complex set of functions. We have considered visually impaired personnel in terms of physical limitations and the community who falls in the older age limit as our target community. Our user study has confirmed that the visually impaired user community here asks for a simple and functional interface. We have designed, developed, and deployed a simple system ifreePhony that captures the minimalistic features. We have considered both the elderly and the visually impaired community in our user studies. It shows around 36% reduction in search time and around 57% increase in text typing compared to a traditional phone.